Pedagogical strategies for the development of training skills in research. How to mitigate the absence of reading of students in Social Sciences (Revista Innova Educación, 2020)
The objective was to understand the training process in research as an academic practice, raising the need for strategies in the face of the weak habit of reading in training settings that allow us to respond to the crisis of interpretation of social problems. This reflection was raised from the phenomenological-hermeneutic method with a social-critical approach in a period of 2 years, training and accompanying 436 students with 145 proposals of formative research, collecting information through 5 semi-structured interviews with teachers and 50 student surveys. Therefore, this reflection is the starting point of a pedagogical proposal that promotes reading and critical reflection exercises. Consequently, the social sciences must formulate research routes that cross the curriculum, seeking in turn to guide and enhance the work of students in research procedures.
Keywords: Research, Reading habits, Critical Reflection, Pedagogical Practice.